1993
DOI: 10.2503/jjshs.62.103
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Occurrence of Hollowing in Watermelon and the Size and the Number of Fruit Cells and Intercellular Air Spaces.

Abstract: Hollowing (formation of a central cavity) in watermelons plagues the growers by reducing their market values. This paper reports the relationship between the occurrence of this disorder and fruit weight, cell size and number, and the volume of the intercellualr air spaces as by a) nodal position of the fruit, b) NAA application, and c) partial defoliation of the bearing. Fruits borne on the lower, basal nodes (Treatment L) were lighter at harvest than those borne on higher, distal nodes (Treatment H) but the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
0
14
1
Order By: Relevance
“…38 Future research on the relationships between spatial/temporal patterns of citrulline accumulation and cell anatomy in watermelon fruits will be important to understand citrulline metabolism in watermelon. Hollowing (formation of a central cavity) in the fruits is another phenomenon commonly observed during watermelon maturation, 39 although cavity formation in mature fruits was not observed in the present study.…”
Section: Accumulation Pattern Of Total Proteins and Citrullinecontrasting
confidence: 68%
“…38 Future research on the relationships between spatial/temporal patterns of citrulline accumulation and cell anatomy in watermelon fruits will be important to understand citrulline metabolism in watermelon. Hollowing (formation of a central cavity) in the fruits is another phenomenon commonly observed during watermelon maturation, 39 although cavity formation in mature fruits was not observed in the present study.…”
Section: Accumulation Pattern Of Total Proteins and Citrullinecontrasting
confidence: 68%
“…Internal pressure during rapid fruit growth causes hollowing of the fruit flesh of tomatoes and watermelons (Kano 1993). In prune fruit, Sterling (1953) found that the formation of a gum duct was initiated during the rapid growth stage just before fruit maturation (Stage III).…”
Section: Discussionmentioning
confidence: 99%
“…Optimum temperature for growth of watermelon is 25 to 30°C during the day and 16 to 20°C during the night (Saito, 1991). Cell division in watermelon fruit stops at 6 DAA (Kano, 1993). In this experiment, watermelon fruits were treated after 6 DAA.…”
Section: Discussionmentioning
confidence: 99%